Association between FAS gene −670 A/G and −1377 G/A polymorphisms and the risk of autoimmune diseases: a meta-analysis. Issue 1 (6th January 2020) - Yan, Hongwei; Hong, Yuxiao; Cai, Yunfei
Abstract: Objectives: FAS plays a critical role in the extrinsic apoptosis pathway in autoimmune diseases. Previous studies investigating the association between FAS gene −670 A/G and −1377 G/A polymorphisms and the risk of autoimmune diseases reported controversial results. We performed the meta-analysis to evaluate the possible association. Methods: Relevant studies were identified by searching the PubMed, Embase, CNKI, and Wanfang databases up to December 2018. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated to determine the association. Results: A total of 43 articles including 67 studies (52 studies for FAS −670 A/G and 15 studies for −1377 G/A) were included in the meta-analysis. Our meta-analysis showed that the FAS −670 A/G polymorphism was associated with the risk of autoimmune diseases (GG vs. GA: OR = 1.079, 95% CI = 1.004–1.160, P =0.038), especially in Caucasians (GG vs. GA: OR = 1.12, 95% CI = 1.03–1.23, P =0.012), Asians (G vs. A: OR = 0.89, 95% CI = 0.83–0.96, P =0.002), systemic lupus erythematosus (SLE) (G vs. A: OR = 0.85, 95% CI = 0.77–0.94, P =0.001), multiple sclerosis (MS) (GG+GA vs. AA: OR = 0.83, 95% CI = 0.70–0.99, P =0.043), systemic sclerosis (SSc) (GG vs. GA: OR = 1.20, 95% CI = 1.07–1.36, P =0.003) and Hashimoto's thyroiditis (HT) (G vs. A: OR = 1.45, 95% CI = 1.10–1.90, P =0.008); the FAS −1377 G/A polymorphism was associated with the risk of autoimmune diseases (A vs. G: OR = 1.11, 95% CI = 1.03–1.20, P =0.008), especially in Asians (A vs. G: OR = 1.15, 95% CI = 1.05–1.25, P =0.002) and high quality studies (A vs. G: OR = 1.14, 95% CI = 1.05–1.24, P =0.002). Conclusion: This meta-analysis demonstrated that the FAS –670A/G and –1377 G/A polymorphisms were associated with the risk of autoimmune diseases.